Facial Reconstruction After Mohs Surgery: A Critical Review of Defects Involving the Cheek, Forehead, and Perioral Region. Issue 2 (March 2019) - Johnson, Anna R.; Egeler, Sabine A.; Wu, Winona W.; Bucknor, Alexandra; Ibrahim, Ahmed M.S.; Lin, Samuel J.
Abstract : Abstract: Facial defects following Mohs surgery can cause significant functional, cosmetic, and psychologic sequelae. Various techniques for nasal reconstruction after Mohs surgery have been analyzed in the medical literature, yet there has been less attention given to procedures for other crucial facial aesthetic regions. A literature search using PubMed, EMBASE, and ISI Web of Science for studies assessing reconstructive techniques of the forehead, cheek, and perioral regions after Mohs surgery was performed. No limitations on date or language were imposed. Studies meeting inclusion criteria consisted of an entirely post-Mohs population, specified technique for aesthetic unit reconstruction, and detailed complications. The initial search yielded 2177 citations. Application of the author's inclusion and exclusion criteria resulted in 21 relevant studies. Linear closure was highlighted as the predominant technique when possible in all 3 aesthetic zones. Local flaps remained the workhorse option for cheek and forehead defects. Cheek and perioral reconstruction were associated with higher complication rates. Eighty-one percent of studies did not include patient-reported outcomes or standardized outcome measurement assessments. Mohs surgery has become a valuable approach for treatment of skin malignancies of the face. This review has identified significant study heterogeneity in methodology, design, and outcome assessment. Currently, there is no evidence-based literature to support an algorithm to guide surgeon choice of treatment in these 3 central areas. Recommendations are provided to improve the quality of future studies to better inform appropriate surgical technique for each facial unit analyzed.